Análisis de la calidad del servicios turísticos que ofrece el hostal inca de la ciudad, cantón, y provincia de Loja - Vargas Carrión, Jessica Anahí (2022)
The general objective of the research is the analysis of the quality of the services provided by the Inca hostel in the city of Loja, for the fulfillment of the same three specific objectives are proposed, the first objective: To diagnose the current situation of the hostel. "Inca" in the City, Canton and Province of Loja, the second objective: Evaluate the quality of the service offered by the Hostel "Inca" of the City, Canton and Province of Loja and the third objective: Develop an improvement plan in the quality of the tourist service for the hostel "Inca" of the City, Canton and Province of Loja. The Inca hostel is taken as an object of study for being an establishment that has been in the field of accommodation in the city of Loja for several years. In order to achieve the objectives, a literature review was carried out to form a conceptual framework of the issues involved in an analysis of the quality of services, regulations, permits and obligations based on a tourist establishment, as well as a reference framework for know the environment where the research was carried out and know the characteristics of the hostel which is being investigated. The methodology used was descriptive in nature, which allows knowing the phenomenon or process for which the materials were used as office supplies, technological equipment, business or institutional resources, as well as methods such as the descriptive and the ServQual model, for the collection of information. Techniques such as interview, survey, direct observation and SWOT matrix were used. To diagnose the current situation of the Inca hostel, a matrix was applied to collect information in order to identify how the hostel is currently, allowing to collect general information, legal regulations of the Inca hostel, as well as an analysis of the services it offers. Based on the tourist accommodation regulations issued by MINTUR, an interview was applied to the main agents involved within the hostel. To evaluate the quality of the service, it was based on the ServQual model with the existing gap between the expectations and perceptions that the client has before and after receiving the service, for which a survey with 28 statements was used, 6 of 5 them of personal information of the surveyed and 22 using the Servqual model, based on five dimensions identified as tangibility, reliability, empathy, responsiveness and security, in order to measure a 5-point Likert scale was used. The results were that the Hostal Inca must: carry out a redesign of the reception area, propose a loyalty plan for the clients of the hostel, carry out a training plan for the employees of the Hostal "Inca", carry out a manual of functions for customer service . At the end of the investigation, conclusions and recommendations were obtained that allow the present work to be synthesized, the most significant conclusion is that in a general analysis of the Hostel, it is that the expectations exceed the perception of the client, with a rating of 4.61 points out of 5, while the perception of 4.52 out of 5 points. It is observed that the rating of the services received is corresponding to very satisfied, which is not bad, but it is always necessary to seek to improve the quality of the service in order to have a higher rating. The most important recommendation is that the proposals be taken into account by the owner since they are directly focused on improving the provision of services, aiming at the quality of those offered. The research serves as the basis for future research and is applicable to any establishment of tourist accommodation since the information obtained is real and verified, it serves to carry out a broader approach to the quality of the service offered by the Hostels of the city of Loja to expand it. to accommodation establishments in various sectors and to be able to make comparisons with all establishments in the area.